2017
DOI: 10.1111/jace.14613
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and first‐principles study of Ti–C–O system: Interplay of thermodynamic and structural properties

Abstract: The thermodynamic properties and vacancy formation mechanism of Ti–C–O system were investigated by means of empirical calorimetry method and first‐principles calculations. The heat of combustion of titanium oxycarbides (TiC1−xOx, 0≤x≤1) solid solution were first measured by burning the materials in oxygen bomb calorimeter through sophisticated design experimental environment. The mixing enthalpy of the reaction (1−x)TiC + xTiO=TiC1−xOx was further calculated based on the measured data. Mixing enthalpy was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…Furthermore, there was a tendency for the number of nonmetallic inclusions to decrease as the sum of the carbon and oxygen concentrations decreased, which is consistent with the results in the literature [3,9]. with oxygen, and the lattice constant is slightly smaller than TiC [16,17]. Thus, the titanium carbides are referred to as Ti(C,O) in this paper.…”
Section: Measurement Of Nonmetallic Inclusions and Surrounding Defectssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, there was a tendency for the number of nonmetallic inclusions to decrease as the sum of the carbon and oxygen concentrations decreased, which is consistent with the results in the literature [3,9]. with oxygen, and the lattice constant is slightly smaller than TiC [16,17]. Thus, the titanium carbides are referred to as Ti(C,O) in this paper.…”
Section: Measurement Of Nonmetallic Inclusions and Surrounding Defectssupporting
confidence: 90%
“…Note that the TiC peaks in Figure 3 are slightly shifted to a higher angle compared with the TiC data (00-32-1383) from the International Centre for Diffraction Data. This is because the TiC in the samples has a composition where some of the carbon has been replaced with oxygen, and the lattice constant is slightly smaller than TiC [16,17]. Thus, the titanium carbides are referred to as Ti(C,O) in this paper.…”
Section: Measurement Of Nonmetallic Inclusions and Surrounding Defectsmentioning
confidence: 99%
“…All of the peaks for TiC were shifted to a slightly higher angle compared with ICDD:32-1383. It is known that the lattice constants become smaller and this kind of peak shift occurs when oxygen is substituted for some of the carbon in TiC [26], and we also observed the same phenomenon in a previous study [13]. Toro et al [4] and Ito et al [17] also reported that oxygen and nitrogen are contained in TiC in Ti-Ni alloy.…”
Section: Resultssupporting
confidence: 88%
“…mental data in the previous reference. 15) Therefore, the inclusions in the NiTi alloys produced under these conditions appear to be TiC 1−x O x (x = 0.4). More generally, the inclusions in NiTi alloys have been reported to be composed of Ti (C, N, O) x 2,5) and Ti 4 Ni 2 O x .…”
Section: Identi Cation Of Inclusion Phasementioning
confidence: 96%
“…Jiang et al performed XRD measurements for synthetic samples of TiC 1−x O x with varying x and estimated the lattice parameters with the changing value of x. 15) As shown in Table 3, the average (200) distance was 0.2147 nm and the lattice parameter was 0.4294 nm, which corresponds to a value of x = 0.4 according to the experi- Fig. 8 Relationship between the thickness of the nonmetallic inclusions and the thermal conductivity of the cooling blocks.…”
Section: Identi Cation Of Inclusion Phasementioning
confidence: 99%